Impact of the thermomechanical load on subsurface phase transformations during cryogenic turning of metastable austenitic steels - Hendrik Hotz; Benjamin Kirsch; Jan C. Aurich (Journal of Intelligent Manufacturing, 2020)
When machining metastable austenitic stainless steel with cryogenic cooling, a deformation-induced phase transformation from γ-austenite to α′-martensite can be realized in the workpiece subsurface. This leads to a higher microhardness and thus improved fatigue and wear resistance. A parametric and a non-parametric model were developed in order to investigate the correlation between the thermomechanical load in the workpiece subsurface and the resulting α′-martensite content. It was demonstrated that increasing passive forces and cutting forces promoted the deformation-induced phase transformation, while increasing temperatures had an inhibiting effect. The feed force had no significant influence on the α′-martensite content. With the proposed models it is now possible to estimate the α′-martensite content during cryogenic turning by means of in-situ measurement of process forces and temperatures.
Keywords: 620; Martensite; Cryogenic turning; Metastable austenitic steel; Deformation-induced phase transformation